PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Johannes .; Edward .; Budi Aryanto (Jurnal Dinamika Manajemen, 2014)
This study purpose is to examine the influence of leadership styles and organizational culture on employee performance. Sample consists of 80 employees. Data collection used a structured questionnaire and applies 5 point Likert scale. The results show that the leadership style and organizational culture simultaneously contributed to the variance of performance as much as 84.5%. Furthermore, partially, the two variables, leadership styles and organizational culture significantly affect the employee performance. Hence, organization should consider improving leadership style and organizational culture simultaneously in order to improve employee performance. Â  Key Words. Food Securiy Agency, Lakip, Provinsi Jambi Â